Analisis Kesulitan Belajar Matematika Siswa pada Materi Barisan dan Deret Kelas XI SMK Karya Nasional Kuningan - Wahyu Khairullah; Tio Heriyana (Indo-MathEdu Intellectuals Journal, 2023)
This research was motivated by the attention of the author who found the fact that almost all students today are more indifferent in doing math problems because of difficulties in the process of solving the problems they face. Therefore, the purpose of this study is to find out how the difficulties experienced by students when learning mathematics and the factors that influence it. This research was carried out at SMK Karya Nasional Kuningan which took place from March to May 2023. The subjects of this study were grade XI students of SMK Karya Nasional with the samples used were industrial class and business class students selected based on the consideration of mathematics teachers. The instruments used in this study are observation guidelines, interview guidelines and document collection. This research is qualitative research whose research procedure produces descriptive data using a phenomenological approach. The results showed that students have various difficulties learning mathematics, this is due to many factors that influence students in learning mathematics. Teacher strategies in carrying out the learning process play an important role in order to optimize the classroom environment to increase learning motivation, increase interest, and build confidence in students